Electronic intracavitary brachytherapy quality management based on risk analysis: The report of AAPM TG 182. Issue 4 (29th December 2019) - Thomadsen, Bruce R.; Biggs, Peter J.; Cardarelli, Gene A.; Chu, James C. H.; Cormack, Robert A.; Feng, Wenzheng; Heaton, H. Thompson; Hiatt, Jessica R.; Law, Jonathan N.; Limmer, Jeffery P.; Ouhib, Zoubir; Pai, Sujatha; et al.
Abstract : Purpose: The purpose of this study was to provide guidance on quality management for electronic brachytherapy. Materials and Methods: The task group used the risk‐assessment approach of Task Group 100 of the American Association of Physicists in Medicine. Because the quality management program for a device is intimately tied to the procedure in which it is used, the task group first designed quality interventions for intracavitary brachytherapy for both commercial electronic brachytherapy units in the setting of accelerated partial‐breast irradiation. To demonstrate the methodology to extend an existing risk analysis for a different application, the task group modified the analysis for the case of post‐hysterectomy, vaginal cuff irradiation for one of the devices. Results: The analysis illustrated how the TG‐100 methodology can lead to interventions to reduce risks and improve quality for each unit and procedure addressed. Conclusion: This report provides a model to guide facilities establishing a quality management program for electronic brachytherapy.